2014
DOI: 10.1136/bcr-2014-204552
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella-related urinary tract infection in an elderly patient

Abstract: SUMMARYAn elderly female patient with an uncomplicated urinary tract infection from Salmonella newport is presented. Radiological and laboratory studies were performed because of her systemic and exposure risk factors as well as prior urinary tract abnormalities. While this patient was successfully treated as an outpatient with oral antibiotics, complications and recurrence are common and deserve close follow-up with repeat urine cultures at a minimum. Further laboratory and radiological testing should be guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…were found to be involved in some UTI cases in this study. These bacteria are uncommon human pathogens and as a result, the infection cases are rare (29,30). The former is commonly acquired in humans through the ingestion of improperly preserved fish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…were found to be involved in some UTI cases in this study. These bacteria are uncommon human pathogens and as a result, the infection cases are rare (29,30). The former is commonly acquired in humans through the ingestion of improperly preserved fish.…”
Section: Discussionmentioning
confidence: 99%
“…As regards Salmonella spp., this group of bacteria is generally responsible for typhoid fever. Many reports outlined their implication in UTIs, especially nontyphoidal strains (30,32). Similarly, this pathogen constitutes another health concern as Salmonella UTI which may complicate pyelonephritis, kidney failure, renal lithiasis, and chronic bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) the risk of recurrent or chronic asymptomatic bacteriuria with shorter treatment regimens; and (3) the concern for antibiotic resistance in carriers despite normally appropriate treatment. 15 For doubly resistant strains (as in our patient), cefixime is recommended. With regard to the urinary carrier state, mechanical pathology of the urinary tract must be corrected.…”
Section: Discussionmentioning
confidence: 92%
“…Two previous studies demonstrated low frequencies (1.4 to 2.8%) of Salmonella isolated from urine in comparison with other clinical samples (mainly enteric) in the São Paulo state, Brazil [14,15]. Despite this low occurrence, both old and recent scientific studies have reported the association of Salmonella in urine cultures with UTIs, mainly in immunocompromised and elderly hospitalized patients [16][17][18][19][20]. In the present study, we described 38 Salmonella isolates (all of them NTS) obtained from urine cultures of patients from seven different hospitals, five from Porto Alegre (the capital city) and two from two other important and populous cities of the Rio Grande do Sul state (Novo Hamburgo and Santa Maria).…”
mentioning
confidence: 98%